Analisis Kadar Kalsium, Zat Besi dan Daya Terima Cookies Ikan Seluang (Rasbora sp) Kacang Tunggak (Vigna unguiculata) sebagai Makanan Selingan Anemia Remaja Perempuan - Solteria Tumongka; Nany Suryani; Ermina Syainah; Sigit Yudistira (HB PRESS, 2022)
Seluang fish and cowpea are one of foods high in calcium and iron, and thereby they can be used to treat anemia in adolescent girls. A total of 100 g of seluang fish contains 80 mg calcium and 4,7 mg iron. A total of 100 g of cowpea contains 77 mg calcium and 6,50 mg iron which are high enough to be used as a basic ingredient for cookies. This study aimed to determine the differences in the calcium and iron contents and acceptability of cookies made from seluang and cowpea in all treatments. This study used the pure experimental design with a completely randomized design (CRD) with four treatments and three times replication with the proportions of wheat flour, seluang fish, and cowpea as follows: P0 (100%:0%:0%), P1 (65%:25%:10%), P2 (65%:20%:15%), and P3 (65%:15%:20%). Calcium and iron contents were analyzed using the One-Way Anova while the acceptability was analyzed using the Friedman test. The results showed that there were differences in calcium content in all treatments (p<0,001) and the highest calcium content was found in P1 (32,62 g) while the highest iron content was found in P1 (2,17 g). There was no difference in iron content in all treatments (p=0,185). The addition of seluang fish and cowpea affected the acceptability of cookies in all treatments, indicated by the significance value of each aspect as follows: color (p<0,001), aroma (p<0,001), texture (p<0,001), taste (p<0,001).